The population of donkeys and mules in Brazil according to agricultural censuses from 1960 to 2017 - Mariana Ramos Queiroz; Mariana Bombo Perozzi Gameiro; Adroaldo José Zanella (Brazilian Journal of Veterinary Research and Animal Science, 2021)
To better understand and manage the population of donkeys and mules, it is essential to know information about its size. In developing countries, these animals are often used as working animals, mainly by poor populations in agricultural and livestock labor, but their use is decreasing in Brazil. Brazilian official data regarding donkeys and mules started to be measured at the agricultural census of 1960 and, from that time, eight agricultural censuses were published. But until the writing of this paper, no scientific paper was dedicated to the analysis of the results of the official agricultural censuses on the population of donkeys and mules in Brazil. Thus, we aim to compile and analyze the official Brazilian data from 1960 until 2017 to enhance the actions of stakeholders, researchers, and decision-makers concerned with Brazilian donkeys and mules.